2022
DOI: 10.3390/healthcare10122412
|View full text |Cite
|
Sign up to set email alerts
|

Problems Associated with Co-Infection by Multidrug-Resistant Klebsiella pneumoniae in COVID-19 Patients: A Review

Abstract: To date, coronavirus disease 2019 (COVID-19) and its variants have been reported as a novel public health concern threatening us worldwide. The presence of Klebsiella pneumoniae in COVID-19-infected patients is a major problem due to its resistance to multiple antibiotics, and it can possibly make the management of COVID-19 in patients more problematic. The impact of co-infection by K. pneumoniae on COVID-19 patients was explored in the current review. The spread of K. pneumoniae as a co-infection among critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“… 55 59 This model can assess the ability of therapeutics to treat a type of infection where treatment is complicated by biofilm formation. 5 , 60 , 61 Initially, we assessed the toxicity profile of bac7 (1–35) to validate the absence of general mammalian cell cytotoxicity ( Figure S7 ; Table S1 ). Our hemolysis results revealed bac7 (1–35) has a limited ability to lyse red blood cells, as we did not see an increase in lysis as we increased the concentration of peptide ( Figure S7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 55 59 This model can assess the ability of therapeutics to treat a type of infection where treatment is complicated by biofilm formation. 5 , 60 , 61 Initially, we assessed the toxicity profile of bac7 (1–35) to validate the absence of general mammalian cell cytotoxicity ( Figure S7 ; Table S1 ). Our hemolysis results revealed bac7 (1–35) has a limited ability to lyse red blood cells, as we did not see an increase in lysis as we increased the concentration of peptide ( Figure S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…This rebounding observed with the gold standard for topical treatment is very intriguing considering the increase in polymyxin B resistance in recent years. 5 , 68 , 69 Although our in vivo testing was limited in this study, it begins to reveal the potential of our peptide for wound treatment. Our future studies will focus on therapeutic optimization of bac7 (1–35) to increase the selectivity index and broaden the in vivo testing to include longer time intervals between infection and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial coinfection among recruited patients was commonly caused by gram-negative bacterial species, including K pneumoniae and A baumannii as evidenced in other similar studies. [ 11 , 27 ] These bacterial species are frequently linked with multidrug resistance (MDR) and treatment failure. Thus, coinfection caused by K pneumoniae or/and A baumannii would be more serious and challenging due to the higher rate of treatment failure, severe complications and death.…”
Section: Discussionmentioning
confidence: 99%
“…E. bugandensis is a common human commensal [43,44] but can act as an opportunistic pathogen, co-infecting immunocompromised individuals (e.g. COVID-infected patients) [45], and have the ability to transfer plasmids through HGT events [46,47]. Studies have also demonstrated the co-presence of Enterobacter, Klebsiella, Paenibacillus, and Pantoea as bacterial endophytes in cereals and Enterobacter sp., Mixta sp., and Pantoea sp.…”
Section: Discussionmentioning
confidence: 99%